2014
DOI: 10.1111/apha.12313
|View full text |Cite
|
Sign up to set email alerts
|

On the antioxidant properties of erythropoietin and its association with the oxidative-nitrosative stress response to hypoxia in humans

Abstract: These findings demonstrate that EPO has the capacity to act as a biological antioxidant and provide a mechanistic basis for its reported cytoprotective benefits within the clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…In humans, preliminary work showed that Epo can reduce the infarct size following an acute stroke by penetrating the blood-brain barrier, but the authors failed to replicate their results during a more extensive trial (Ehrenreich et al 2009). The work from Bailey et al (2014) published here sheds a new light on the aforementioned studies. Indeed, while these studies assumed that the effects of (rHu)Epo are secondary to activation of gene expression, it now appears that Epo could also mitigate the acute inflammatory response thanks to its antioxidant properties.…”
Section: The Janus Face Of Epo; Adaptive Aspectsmentioning
confidence: 65%
See 3 more Smart Citations
“…In humans, preliminary work showed that Epo can reduce the infarct size following an acute stroke by penetrating the blood-brain barrier, but the authors failed to replicate their results during a more extensive trial (Ehrenreich et al 2009). The work from Bailey et al (2014) published here sheds a new light on the aforementioned studies. Indeed, while these studies assumed that the effects of (rHu)Epo are secondary to activation of gene expression, it now appears that Epo could also mitigate the acute inflammatory response thanks to its antioxidant properties.…”
Section: The Janus Face Of Epo; Adaptive Aspectsmentioning
confidence: 65%
“…1 -'Traditional'). Just as one could have thought that we knew everything about this molecule, Bailey et al (2014) have demonstrated that recombinant Epo (rHuEpo) can equally serve as a very potent antioxidant (see Fig. 1 -'Evolving').…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies found the recombinant form of EPO (rHuEPO) to be a potent scavenger of HO˙with the capacity to inhibit Fenton chemistry through catalytic iron chelation. Its ability to scavenge peroxyl (ROO˙) radicals, evaluated in vitro, was also superior compared to other antioxidants (5). The indirect antioxidant EPO action could be achieved through iron depletion and thus limitation of iron-dependent oxidative injury, and by increasing new red blood cells (RBC) loaded with a significant amount of antioxidants (1,2,11,16).…”
Section: Discussionmentioning
confidence: 99%